Perceived stress, social support, emotional intelligence, and post-stress growth among Chinese left-behind children: a moderated mediation model - Zhang, Lyuci; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Jiang, Yuqin; Wu, Sumei; Chen, Ye (MDPI, 2022)
Background: Several previous studies have revealed a negative impact of perceived stress on post-stress growth. Nevertheless, the potential mediating and moderating mechanisms are unclear, particularly for left-behind children in China. Therefore, this study aims to investigate the negative relationship between perceived stress and post-stress growth, the mediating effect of social support, as well as the moderating effect of emotional intelligence in a sample of Chinese left-behind children. Methods: A sample of 837 Chinese students in elementary and middle school was collected for this study. The Perceived Stress Scale, the Social Support Scale, the Emotional Intelligence Scale, and the Post-Stress Growth Scale were employed to examine them. The data were analyzed using SPSS 25.0 software. Results: The results indicate a significant negative association between perceived stress and post-stress growth. Among perceived stress and social support, the former acted as a mediator, while the latter as a moderator. This study sheds light on the post-stress growth of Chinese left-behind children. The findings validated a model of moderated mediation that shows the relationship between perceived stress, emotional intelligence, social support, and post-stress growth. Conclusion: This study confirmed that social support is one of the most important factors among left-behind children, from perceived stress to post-stress growth. Furthermore, the study reveals that emotional intelligence can adjust the relationship between perceived stress and social support to post-stress growth. Therefore, for both family education and school education, the result provides a new direction.